Role of EGF Receptor Regulatory Networks in the Host Response to Viral Infections - Carlin, Cathleen R. (Frontiers in Cellular and Infection Microbiology, 2022)
In this review article, we will first provide a brief overview of EGF receptor (EGFR) structure and function, and its importance as a therapeutic target in epithelial carcinomas. We will then compare what is currently known about canonical EGFR trafficking pathways that are triggered by ligand binding, versus ligand-independent pathways activated by a variety of intrinsic and environmentally induced cellular stresses. Next, we will review the literature regarding the role of EGFR as a host factor with critical roles facilitating viral cell entry and replication. Here we will focus on pathogens exploiting virus-encoded and endogenous EGFR ligands, as well as EGFR-mediated trafficking and signaling pathways that have been co-opted by wild-type viruses and recombinant gene therapy vectors. We will also provide an overview of a recently discovered pathway regulating non-canonical EGFR trafficking and signaling that may be a common feature of viruses like human adenoviruses which signal through p38-mitogen activated protein kinase. We will conclude by discussing the emerging role of EGFR signaling in innate immunity to viral infections, and how viral evasion mechanisms are contributing to our understanding of fundamental EGFR biology.